2022
DOI: 10.11159/tann22.139
|View full text |Cite
|
Sign up to set email alerts
|

Formation of NiO Thin-Film via Picosecond Laser Pulses for Energy Storage Electrode Fabrication

Abstract: Consumer demand in portable and mobile electronics has noticed exponential rise leading to increases demand for energy storage devices. Once such device is supercapacitor which relies on interfacial, surface charge storage. With increased surface area, better capacitance is observed with assistance of nanoengineering. In this paper, a thin oxide layer is generated on Ni sheet surface with ultra-short pulses for laser ablation of Ni. The effects of power were analysed by keeping other parameters such as pulse d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…It was shown that at a lower power density of 5 W, the morphology of the surface was uniformly distributed, whereas at the three times the power density of 15 W, close to nanostructures were visible with a non‐uniform surface. This was confirmed by electrochemical tests such as CV, GCD, and EIS which showed 5 and 15 W having excellent electrochemical characteristics 186 …”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 54%
See 1 more Smart Citation
“…It was shown that at a lower power density of 5 W, the morphology of the surface was uniformly distributed, whereas at the three times the power density of 15 W, close to nanostructures were visible with a non‐uniform surface. This was confirmed by electrochemical tests such as CV, GCD, and EIS which showed 5 and 15 W having excellent electrochemical characteristics 186 …”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 54%
“…This was confirmed by electrochemical tests such as CV, GCD, and EIS which showed 5 and 15 W having excellent electrochemical characteristics. 186 By changing the parameters of the laser, it is possible to change the surface properties of the in situ 3D structure allowing to have full control of the morphology and the topology of the structure. Parameters such as power, frequency, pulse duration, and scan speed can be easily altered to form advanced nanostructures.…”
Section: D Self-standing Structure Via Laser Pulse Ionizationmentioning
confidence: 99%